Pedagogical Principles of Development of Innovative Competence of Primary Class Teachers (Journal of Pedagogical Inventions and Practices, 2024)
The article examines the mechanisms of developing the innovative competence of future primary school teachers. Its modern trends are analyzed. Proposals and conclusions on the development of creative thinking ability of teachers are given